Alternatives to physical plant coverage to suppress spontaneous plants in an organic apple system (Research, Society and Development, 2024)
This study aimed at evaluating different alternatives to physical plant coverage to suppress spontaneous plants in an organic production system of apple trees. The experiment, which was conducted at the Embrapa Clima Temperado, Pelotas, Rio Grande do Sul, Brazil, in the 2022/2023 cycle, had a randomized block design with five methods of crowing for plant management: no coverage, manual weeding, straw, cardboard and Tetra Pack® packaging. The following factors were evaluated: suppression of spontaneous plants, height of spontaneous plants, seedling survival, apple tree growth and soil temperature under the influence of plant coverage methods. Suppression of spontaneous plants was higher when Tetra Pack® packaging and cardboard were used as methods of physical coverage. Their performance was similar to the one of manual weeding. When suppression of  spontaneous plants was not carried out, the result was death of 22.2% of plants in the treatment without coverage. Soil temperature was lower when coverage was conducted with straw, cardboard and Tetra Pak® packaging. The use of Tetra Pak® packaging not only controlled and decreased height of spontaneous plants and soil temperature, but also led to apple tree growth similar to the one resulting from manual weeding. The use of Tetra Pak® packaging as physical coverage mitigated the need for management of spontaneous plants and proved to be an efficient alternative method to suppress spontaneous plants in an organic production system of apple trees.